The Impact Of Social Skills Training On The Ability To Cooperate In Early Childhood - Fikri, Mu'tasim; Tegeh, I Made (Universitas Pendidikan Ganesha, 2022)
The problem is that children's cooperative abilities are still low because teachers tend to give individual assignments and rarely give group assignments that allow children to work with their friends. This study analyzes social skill training on the ability to cooperate in group B Kindergarten children. This research is quasi-experimental research using a non-equivalent pretest-posttest control group design. The research population was 69 students—the sample with cluster random sampling technique. The sample of this study amounted to 33 students. The data on the results of the ability to work together was collected using observational techniques, which were analyzed using descriptive statistical analysis techniques and inferential statistics with a t-test. The results of the analysis obtained tcount = 23,425 while at the 5% significance level with dk = 31 the value of ttable = 2,039 so that tcount = 23,425 > ttable = 2,039. Based on the test, then H0 is rejected, which means that the HA hypothesis is accepted, which states that there is a significant effect between the group of children who receive social skills training and children who do not receive social skills training on children's cooperative abilities. The results showed a significant effect on cooperative skills between groups of children who received social skills training and those who did not receive social skills training on cooperative skills in Kindergarten.